Effect of Patients Taking Amlodipine on Urea Levels - Nurhidayati Nurhidayati; Nurul Inayati; Agrijanti Agrijanti (Eduvest - Journal of Universal Studies, 2024)
Background: Hypertension is a condition when blood pressure increases or is often referred to as a “silent killer” because signs and sympotoms occur, usually causing headaches, nosebleeds, irreguler heartbead, fan buzzing in the ears, hypertension is a disease that is often found among elderly. Research Purposes: To determine the effect of patients taking amlodipine on urea levels. Research Methodos: Analytic observational research with cross sectional research design. Used 24 sampels of hypertension who consumend the drug amlodipine and analyzed the data using a non parametric test. Result: The mean results of examining urea levels in patients taking amlodipine were 31,61. Conclusion: There wa a significant effect of patients taking the drug amlodipine on urea levels according to adherence in taking the a p value of 0,003 (p<0,05). The results of blood pressure meansurements of patients taking the drug averaged 145 mg/dl.